2021
DOI: 10.1101/2021.12.22.21268246
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Saliva swabs are the preferred sample for Omicron detection

Abstract: The Omicron variant is characterised by more than 50 distinct mutations, the majority of which are located in the spike protein. The implications of these mutations for disease transmission, tissue tropism and diagnostic testing are still to be determined. We evaluated the relative performance of saliva and mid-turbinate swabs as RT-PCR samples for the Delta and Omicron variants. The positive percent agreement (PPA) of saliva swabs and mid-turbinate swabs to a composite standard was 71% (95% CI: 53-84%) and 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
81
2
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(94 citation statements)
references
References 2 publications
8
81
2
3
Order By: Relevance
“…Prior to the first descriptions of Omicron, reports of RT-PCR from comparisons of nasopharyngeal and oropharyngeal/nares 21 , and nasal and oropharyngeal 22 swabs showed little difference. On the other hand, in symptomatic non-hospitalized patients in South Africa, saliva samples detected Omicron more often than mid-turbinate swabs (100% vs. 86% respectively) 8 which was opposite from the performance reported for previously circulating variants. Similarly, in a pre-print non-peer reviewed publication of a small subset of individuals in a high-risk occupational case cohort, the viral load in saliva specimens peaked 1 to 2 days prior to those observed with nasal swab collections 23 .…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…Prior to the first descriptions of Omicron, reports of RT-PCR from comparisons of nasopharyngeal and oropharyngeal/nares 21 , and nasal and oropharyngeal 22 swabs showed little difference. On the other hand, in symptomatic non-hospitalized patients in South Africa, saliva samples detected Omicron more often than mid-turbinate swabs (100% vs. 86% respectively) 8 which was opposite from the performance reported for previously circulating variants. Similarly, in a pre-print non-peer reviewed publication of a small subset of individuals in a high-risk occupational case cohort, the viral load in saliva specimens peaked 1 to 2 days prior to those observed with nasal swab collections 23 .…”
Section: Discussioncontrasting
confidence: 73%
“…These views have been widely propagated on social media, and been discussed and debated in recent print and televised media [10][11][12] . From a virus perspective, differences in viral tropism and kinetics of Omicron may be different compared to previous variants 7,8 , and adds some credence to the idea that virus may be in different parts of the respiratory system at different times.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Antigen detection from nasal swab samples eventually turned positive several days after symptom onset, suggesting that viral replication may initially localize to the oropharynx prior to transitioning to the nasopharynx. A study by Marais et al also found higher viral loads in saliva compared to paired mid-turbinate swabs but did not follow study participants over time to document a transition 12 . The BinaxNOW™ is currently only approved for use with anterior nares swabs in the US 5 .…”
Section: Discussionmentioning
confidence: 97%
“…Omicron has been shown to infect faster and more efficiently than Delta in human bronchus, but with less severe infection in lung, 2 translating to symptom increase of sore throats and decrease of loss of taste and smell, better detected by saliva than nasal swabs. [3][4][5] To date, the viral dynamics and test performance in the Omicron early infection period have not been described in detail, as it requires cohorts receiving near daily testing to identify cases prior to symptom onset.…”
mentioning
confidence: 99%